2008
DOI: 10.1073/pnas.0805797105
|View full text |Cite
|
Sign up to set email alerts
|

Stress resistance and signal fidelity independent of nuclear MAPK function

Abstract: Elevated external solute stimulates a conserved MAPK cascade that elicits responses that maintain osmotic balance. The yeast highosmolarity glycerol (HOG) pathway activates Hog1 MAPK (mammalian ortholog p38␣/SAPK␣), which enters the nucleus and induces expression of >50 genes, implying that transcriptional upregulation is necessary to cope with hyperosmotic stress. Contrary to this expectation, we show here that cells lacking the karyopherin required for Hog1 nuclear import or in which Hog1 is anchored at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 38 publications
14
169
0
Order By: Relevance
“…CgHog1 becomes phosphorylated but seems not to translocate into the nucleus. In fact, ScHog1 and CaHog1 translocation to the nucleus is not required for the activation of downstream events (Westfall et al, 2008, Lee et al, 2017, Day et al, 2017). Even though CgHog1 upon H 2 O 2 challenge does not enrich in the nucleus, this does not exclude cycling between nucleus and cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…CgHog1 becomes phosphorylated but seems not to translocate into the nucleus. In fact, ScHog1 and CaHog1 translocation to the nucleus is not required for the activation of downstream events (Westfall et al, 2008, Lee et al, 2017, Day et al, 2017). Even though CgHog1 upon H 2 O 2 challenge does not enrich in the nucleus, this does not exclude cycling between nucleus and cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the study has suggested that such regulation diverts metabolic flux from biomass to intermediates of glycerol and therefore ensures stable glycerol flux (Petelenz-Kurdziel et al 2013). Also Westfall et al (2008) have shown that Hog1PP dependence is critical for the glycerol synthesis during hyper osmotic stress. Therefore, in the current model, we assumed that the glycerol synthesis is mainly regulated by the enzyme E and Hog1PP.…”
Section: Metabolite Modulementioning
confidence: 98%
“…The other two mutants that did not include the enzyme dependence on glycerol synthesis indicate that a necessary condition for adaptation is the synthesis of glycerol through enzyme synthesised by transcriptional Hog1PP. It should be noted that near-perfect adaptation may not be necessary for the survival of cell, hence non-transcriptional effect of Hog1PP may be sufficient for the cell to survive (Westfall et al 2008). The utility of Hog1PP in glycerol synthesis in addition to the enzyme dependence (i.e.…”
Section: Significance Of Feedbacks In the Glycerol Synthesis Processmentioning
confidence: 99%
“…It is also a popular pathway in yeast for benchmark studies. The kinase activity of Hog1 in the cytoplasm leads to the production of glycerol (Westfall et al, 2008), which allows the cells to equilibrate interior and exterior osmotic pressures (Fig. 2).…”
Section: Parametrically Different Three-dimensional Systemsmentioning
confidence: 99%